LEGAL EFFORTS TO SETTLE CONSUMER DISPUTES IN TRANSACTIONS BASED ON THE CONSUMER PROTECTION LAW - Elli Ruslina (SEAN Institute, 2023)
The success of a transaction often depends on the balance of information and fairness between consumers and business actors. Therefore, this research will examine the role of the Consumer Protection Law in guaranteeing consumer rights and providing a legal framework for effective dispute resolution. The research methodology used is normative legal research which involves collecting data through literature study, analysis of related legal documents, and field research to obtain a comprehensive picture of consumer dispute resolution practices. The research results highlight the need for improvements in e-commerce transaction dispute resolution regulations, especially in the cross-border context. The Consumer Protection Law in Indonesia provides a significant legal basis, but there are obstacles in resolving cross-border disputes. Online Dispute Resolution (ODR) as a potential solution is also not fully optimal. This legal vacuum creates legal uncertainty that can harm the parties, so more specific legal reform is needed. Increasing the role of ODR with the application of more sophisticated technology is the key to resolving e-commerce transaction disputes effectively, while ensuring that the rights of consumers and business actors are well protected.